2020
DOI: 10.3390/su12145654
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Framework for Assessing Context-Specific Rural Livelihood Vulnerability

Abstract: Reviewing both conceptual and empirical studies on climate vulnerability and adaptation assessment, this paper offers an analytical framework to help better understand how context-specific adaptation strategies could be developed. The framework systematically assembles the Sustainable Rural Livelihoods and the Vulnerability Assessment frameworks to develop its structural and analytical components. The resulting five-step approach involves: (i) identification of context along with understanding what aspect of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 168 publications
0
16
0
Order By: Relevance
“…2) that will enable a holistic perspective of various factors that together explain how small-scale farmers can most effectively face climate change incidents. Climate vulnerability is a diverse and nuanced policy issue that interacts with global, regional, national, local, social, political, economic, and ecological variables (Rahman and Hickey, 2020). Consequently, the understanding of climate risk varies from sector to context (Jurgilevich et al, 2017).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…2) that will enable a holistic perspective of various factors that together explain how small-scale farmers can most effectively face climate change incidents. Climate vulnerability is a diverse and nuanced policy issue that interacts with global, regional, national, local, social, political, economic, and ecological variables (Rahman and Hickey, 2020). Consequently, the understanding of climate risk varies from sector to context (Jurgilevich et al, 2017).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Consequently, the understanding of climate risk varies from sector to context (Jurgilevich et al, 2017). Despite the complex nature of first, local resource usage and delivery patterns (Adger et al, 2006), and second, the degree of ambiguity regarding livelihoods related to climate variability (Rahman and Hickey, 2020).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor governance constitutes another key driver of vulnerability. This broad category encompasses lack of representation or outright discrimination, rampant political corruption, underdeveloped property rights, unsustainable resource management, formal institutions founded on clientelism, weak rule of law, and widespread violence (55)(56)(57). One early study that sought to rank the relative importance of generic vulnerability factors concluded that aspects of governance, notably effectiveness and accountability, were the most decisive in determining disaster-related loss of human lives (35).…”
Section: Political Determinants Of Vulnerabilitymentioning
confidence: 99%